Engineering CD20 CARs with a Twist - Scheller, Lukas; Hudecek, Michael (Cancer Immunology Research, 2023)
CD20 is highly expressed in several types of B-cell lymphoma and is an intuitive target for chimeric antigen receptor (CAR) T-cell therapy. However, with conventional approaches, it has been challenging to provide CD20 CAR designs that confer efficacy in preclinical models and in clinical trials. In this issue, Chen and colleagues report several improved CD20 CARs, developed with minimal deviations from conventional design principles, that confer curative anti-lymphoma efficacy in preclinical models. These novel CD20 CARs enrich the pipeline for clinical development and provide an example of rational CAR design that is informed by insights into the structural biology of CAR domains. See related article by Chen et al., p. 150 (3).
CRIS-Team Scopus Importer:2023-03-23